Catecholamine Surges Cause Cardiomyocyte Necroptosis via a RIPK1–RIPK3-Dependent Pathway in Mice - Wu, Penglong; Cai, Mingqi; Liu, Jinbao; Wang, Xuejun (Frontiers in Cardiovascular Medicine, 2021)
Background: Catecholamine surges and resultant excessive β-adrenergic stimulation occur in a broad spectrum of diseases. Excessive β-adrenergic stimulation causes cardiomyocyte necrosis, but the underlying mechanism remains obscure. Necroptosis, a major form of regulated necrosis mediated by RIPK3-centered pathways, is implicated in heart failure; however, it remains unknown whether excessive β-adrenergic stimulation-induced cardiac injury involves necroptosis. Hence, we conducted the present study to address these critical gaps. Methods and Results: Two consecutive daily injections of isoproterenol (ISO; 85 mg/kg, s.c.) or saline were administered to adult mixed-sex mice. At 24 h after the second ISO injection, cardiac area with Evans blue dye (EBD) uptake and myocardial protein levels of CD45, RIPK1, Ser166-phosphorylated RIPK1, RIPK3, and Ser345-phosphorylated MLKL (p-MLKL) were significantly greater, while Ser321-phosphorylated RIPK1 was significantly lower, in the ISO-treated than in saline-treated wild-type (WT) mice. The ISO-induced increase of EBD uptake was markedly less in RIPK3−/− mice compared with WT mice (p = 0.016). Pretreatment with the RIPK1-selective inhibitor necrostatin-1 diminished ISO-induced increases in RIPK3 and p-MLKL in WT mice and significantly attenuated ISO-induced increases of EBD uptake in WT but not RIPK3−/− mice. Conclusions: A large proportion of cardiomyocyte necrosis induced by excessive β-adrenergic stimulation belongs to necroptosis and is mediated by a RIPK1–RIPK3-dependent pathway, identifying RIPK1 and RIPK3 as potential therapeutic targets for catecholamine surges.